Career Devevolment: Developing A High Performing Workforce - Walean, Ronny Hansje (JBE (Journal of Business and Economics), 2005)
Today’s business environment, driven by changing technology, operating methods, and social forces, has created a need for organization to enchance their career development programs. Changing rechnology and new business methods cause ongoing shifts in job duties, skills, demands, and number of employees need in different types of jobs within organization, therefore, Human Resource Manager must be sensitive to changes in markets, people, and competition and become aware of the need for an adaptive and flexible career program. A good career development program can cintribute to the high-performing organization by utilizing the individual difference among employees motivating them, and also influencing the job satisfaction and productivity. Organization has two primary motives for implementing career development programs: (1) to develop and promote employees from within and (2) to reduce turnover.